Analysis of Communication Services of the CNP LP3I Jakarta Depok Campus Division on Final Year Students in Understanding the Program for Preparing to Enter the World of Work - Wahyuningtias, Dinda Dwimanda; Tomasowa, Gloria Angelita (The Eastasouth Journal of Social Science and Humanities, 2025)
This study aims to analyze the communication of the Cooperation and Placement Division (CNP) of the LP3I Polytechnic Jakarta Depok Campus to final year students in understanding the program to prepare them for entering the world of work using a qualitative approach through case study methods. Data was collected through interviews, observations, and documentation, then analyzed using the Service-Dominant Logic (SDL) theory by Vargo and Lusch and Joseph A. DeVito's interpersonal communication theory. The results of the study show that the CNP Division's service communication is effective through a combination of digital and face-to-face communication that is two-way, dynamic, and adaptive to student needs, with the main stages being information delivery, personal assistance, structured training, and service evaluation. The implementation of SDL principles is evident in the collaboration between CNP, students, alumni, and industry partners as co-creators of value in creating service value oriented towards work readiness. Interpersonal communication elements such as openness, empathy, support, positive attitude, and equality are important factors that strengthen the relationship between CNP staff and students. Communication barriers such as time constraints, differences in understanding, and low student motivation can be minimized through a personal approach and empathetic communication. In conclusion, the CNP Division plays a strategic role in building an integrative service communication ecosystem between the world of education and the world of work, where effective communication not only increases students' understanding of career preparation programs but also strengthens their interpersonal skills, professionalism, and confidence. It can also serve as a reference for other vocational education institutions in developing a collaborative and value-based service communication model to produce competent graduates who are ready to compete in the world of work.